2018
DOI: 10.1111/acfi.12389
|View full text |Cite
|
Sign up to set email alerts
|

Religiosity and cross‐country differences in trade credit use

Abstract: Using the firm-level data over 1989-2012 from 53 countries, we find religiosity in a country is positively associated with trade credit use by local firms. Specifically, after controlling for firm-and country-level factors as well as industry and year effects, we show that trade credit use is higher in more religious countries. Moreover, both creditor rights and social trust in a country enhance the positive association between religiosity and trade credit use, while the quality of national-level disclosure mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 56 publications
0
14
0
Order By: Relevance
“…In the context of disclosure quality, religiosity is expected to have a positive association with disclosure quality. One aim of disclosure is to mitigate information asymmetry (Chen et al 2020). An ethical firm's manager is more likely to disclose more useful information that helps users in their economic decision-making.…”
Section: Religiosity Formal Institutions and Banks' Disclosure Qualitymentioning
confidence: 99%
See 2 more Smart Citations
“…In the context of disclosure quality, religiosity is expected to have a positive association with disclosure quality. One aim of disclosure is to mitigate information asymmetry (Chen et al 2020). An ethical firm's manager is more likely to disclose more useful information that helps users in their economic decision-making.…”
Section: Religiosity Formal Institutions and Banks' Disclosure Qualitymentioning
confidence: 99%
“…One key informal institution that has captured the attention of researchers is religiosity (Vitell 2009, Cantrell and Yust 2018, Chircop et al 2017, Cui et al 2019, Abdelsalam et al 2020, Hilary and Hui 2009, Chen et al 2020. For instance, a recent survey finds that almost 84% of the world population are classified as belonging to a particular faith or holding a religious belief (Sherwood 2018).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, there is some evidence, showing that alternative factors influence trade credits. Chen et al (2020), employing data from 53 countries, study the influence of cultural context on the trade credits amount. They found that religiosity, as well as creditor rights and social trust, positively impacts the trade credit use among the firms in the country.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Next, this study contributes to the literature relating religion to firm behaviour by focusing on how firms treat their non-shareholder stakeholders. Existing studies have shown that religion can influence decision making regarding corporate finance and corporate governance (Hilary and Hui, 2009;Dyreng et al, 2012;El Ghoul et al, 2012;McGuire et al, 2012;Chen et al, 2020). To supplement this research field, our study addresses the potential role of a founder's religious beliefs in shaping firms' policies regarding their employees based on the upper echelon perspective and organisational imprinting view.…”
Section: Introductionmentioning
confidence: 99%